2021
DOI: 10.1111/jgh.15466
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the coronavirus disease 2019 pandemic on irritable bowel syndrome

Abstract: Background and Aim Gastrointestinal manifestations of the coronavirus disease 2019 (COVID‐19) pandemic may mimic irritable bowel syndrome (IBS), and social distancing measures may affect IBS patients negatively. We aimed to study the impact of COVID‐19 on respondents with self‐reported IBS. Methods We conducted an anonymized survey from May to June 2020 in 33 countries. Knowledge, attitudes, and practices on personal hygiene and social distancing as well as psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 38 publications
0
23
0
1
Order By: Relevance
“…Recent evidence suggests that stress has resulted in an increase in the prevalence of IBS during the COVID‐19 pandemic. 21 Moreover, patients with IBS and high levels of anxiety, such as those included in our study are more likely to be susceptible to severe exacerbations due to aberrant coping strategies 22 , 23 , 24 , 25 and lower levels of resilience, 26 catastrophizing and somatization, 27 potentially explaining the more severe somatic (non‐colonic) symptoms, extreme loss of control and helplessness as well as sleep disturbance among those within the pandemic cohort in our study. While the exact reasons for more sleep disturbance in the pandemic group is unclear, social support during the pandemic restrictions may be a contributory factor.…”
Section: Discussionmentioning
confidence: 82%
“…Recent evidence suggests that stress has resulted in an increase in the prevalence of IBS during the COVID‐19 pandemic. 21 Moreover, patients with IBS and high levels of anxiety, such as those included in our study are more likely to be susceptible to severe exacerbations due to aberrant coping strategies 22 , 23 , 24 , 25 and lower levels of resilience, 26 catastrophizing and somatization, 27 potentially explaining the more severe somatic (non‐colonic) symptoms, extreme loss of control and helplessness as well as sleep disturbance among those within the pandemic cohort in our study. While the exact reasons for more sleep disturbance in the pandemic group is unclear, social support during the pandemic restrictions may be a contributory factor.…”
Section: Discussionmentioning
confidence: 82%
“…A population‐based survey, including 2704 people from 33 countries, revealed that 5% of respondents developed IBS‐like symptoms during the first 3 months of the COVID‐19 pandemic. Patients with IBS prior to the COVID‐19 pandemic (11%) reported significantly worse emotional, social, and psychological well‐being, compared with non‐IBS respondents 47 …”
Section: Covid‐19 and The Alimentary Tract—pathophysiologymentioning
confidence: 99%
“…Patients with IBS prior to the COVID‐19 pandemic (11%) reported significantly worse emotional, social, and psychological well‐being, compared with non‐IBS respondents. 47 …”
Section: Covid‐19 and The Alimentary Tract—pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…When talking out of context of the pandemic, burnout can also be associated with various other diseases, including IBS. 4 Burnout was associated with a 2.41-fold elevated prevalence of IBS after adjusting for potential confounding variables, including job strain. 5 Other studies reported that health workers treating COVID-19 patients experience significantly higher depressive symptoms and burnout than others.…”
mentioning
confidence: 90%